REMEDIAÇÃO DE SOLOS CONTAMINADOS POR METAIS PESADOS USANDO BIOSSURFACTANTE PRODUZIDO A PARTIR DE RESÍDUO AGROINDUSTRIAL - Kummer, Larissa (2014)
High concentrations of heavy metals in the soil can affect the sustainability of ecosystems and the health of humans and animals. The metal availability in the environment is related to the characteristics of each element, historical and source of contamination, as well as the properties of each soil. The presence of more than one element is common in contaminated areas and their interaction can affect their behavior in the environment. Researches have been developed to study the behavior of metals in different types of soils and thus help in cases of remediation. In recent years, the soil washing with biosurfactant has been presented as a promising method of remediation with little or no effect on the physico-chemical and microbiological characteristics of the soil, but the costs of obtaining this biosurfactant are still high, because most manufacturers use artificial means for production. Thus, this study had the objective of evaluating the remediation potential of the biosurfactant obtained from the fermentation of cassava water through the action of the bacteria Bacillus subtilis. This biosurfactant was characterized as surfactin, an anionic lipopeptide. Soils of different origins were used, one of them typical of the southwestern state of Paraná and the other from the northwest. The soils were first evaluated according to their potential for adsorption of the elements copper, zinc and lead in monometallic and multimetalic conditions, representing non-competitive and competitive conditions respectively. This evaluation was carried out by tests of adsorption and application of the matematical models of Langmuir and Freündlich. Soils were characterized chemically, physically and mineralogically. After that, it was performed the process of artificial contamination of these soils for application in the experiments of soil washing with biosurfactant in different conditions, having pH and concentration of biosurfactant solution as the main variables. Furthermore, it was also assessed the adsorption s capacity for metals by biosurfactant in liquid medium. The results showed that metals have different behaviors related to the adsorption and desorption to soil and to the biosurfactant. The soil type is also very important for the efficiency of metal removal. The clay soil showed higher adsorption capacity and therefore lower capacity of metal removal when compared to the sandy soil. In general, the soils showed the following sequence of adsorption capacity: Pb > Cu > Zn. The Pb was the element that less desorved by the washing process. It can also be concluded that, when soils are contaminated by more than one element at the same time, its ability to leach is greater than when the element is alone in the medium. This situation occurs because of differences between the competitive processes that take place in the active sites. The washing experiments showed that the biosurfactant was not able to improve the efficiency of removal of metals. The results obtained by the control treatments (only pure water) had very similar values to those that contained biosurfactant. When the wash solution containing the biosurfactant was in high concentrations, decrease in removel efficiency was found in some of the samples. Analysis of high performance liquid chromatography showed that the biosurfactant was adsorbed to soil samples, which is the consequence of not observing the effectiveness of the extractor in the removal of metals. It is notable, however, that the surfactin obtained has the potential to bind to metals, since the tests of adsorption to metals was confirmed by experiments. According to the results obtained, it can be inferred that the surfactin has greater potential for metal removal in liquid media than in solid medium, because of the lower possibility of adsorption. In soil, the results indicated potential use of this biosurfactant as stabilizing of metals in methods of remediation "in situ".